Studies on effect of induced mutagenesis on Finger millet (Eleusine coracana (L.) Gaertn.) Var- CO 13 in M1 generation - L. Mullainathan, K. Aviya, (Horticultural Biotechnology Research)
The present study was carried out to induce chemical mutagens in Finger millet (Eleusinecoracana(L.) Gaertn.). The seed were subjected to different treatment level of EMS and DES. The parameters like Plant height(cm), Number of leaves per plant, Leaf length (cm/plant), Number of finger per plant, Finger length (cm/plant), Days to first bloom, Yield per plant (g) and 1000 grains weight (g)were observed in M1generation. And the result revealed that, all the parameters except days to first blooming show a dose dependent decrease in both treatments. The LD-50 value was found in 30mM of EMS and 40mM of DES.